Analysis of Leadership Style in Physical Education: A Systematic Literature Review - Wahyu Arbanisa; Adi S (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
Background: It considers how these leadership styles affect participants' motivation, engagement, and performance within the context of sports and fitness learning. Research Objectives: The purpose of this research is to look into the use of Leadership Style in Physical Education. Methods: The PRISMA standards for systematic reviews and meta-analysis were followed in this review investigation. The study must be published within the prior five years, from 2020 to 2024. In the search procedure, the following keywords are used: (1) Leadership Style; (2) Physical Education. The search engines Science Direct (Science Citation Index Expanded; Social Science Citation Index). Finding/Results: From various studies underscore the positive impact of leadership style on psychological safety and innovation behavior among physical education teachers, highlighting the importance of cultivating strong leadership identity and competence among school principals and teachers alike. Conclusion: Analyzing leadership styles in physical education is essential for creating supportive environments and developing leadership skills that promote positive values. It optimizes learning effectiveness, boosts participation, and enhances participant performance by adapting strategies to individual needs. Research highlights the positive impact of specific leadership styles, like transformational leadership, on student satisfaction and engagement, while emphasizing the importance of continuous professional development for teachers to enhance their competencies and leadership effectiveness.